Low‐Generation Polyamidoamine Dendrimers as Drug Carriers for Platinum(IV) Complexes. Issue 12 (15th November 2016) - Sommerfeld, Nadine S.; Hejl, Michaela; Klose, Matthias H. M.; Schreiber‐Brynzak, Ekaterina; Bileck, Andrea; Meier, Samuel M.; Gerner, Christopher; Jakupec, Michael A.; Galanski, Markus; Keppler, Bernhard K.
Abstract : An unsymmetrically carboxylated platinum(IV) analogue of oxaliplatin was coupled to low‐generation polyamidoamine dendrimers (PAMAM) with amino‐terminated surfaces [generations two (G‐2) and four (G‐4)]. 1D and 2D diffusion NMR spectroscopy and high‐resolution HPLC–MS/MS were used to characterise the platinum complexes and drug–dendrimer conjugates. The average loads of platinum(IV) complex per dendrimer were determined by inductively coupled plasma MS (ICP‐MS), and maximum loads of 38 % (six platinum units per dendrimer molecule) for the smaller G‐2 and 34 % (22 platinum units per dendrimer molecule) for G‐4 were obtained. As a result of this loading, the average diameters increased from 26 to 34 Å (30 %, G‐2) and from 46 to 63 Å (38 %, G‐4). The in vitro cytotoxicities of the free platinum(IV) complex, the complex‐loaded dendrimers and the free PAMAM analogues G‐2 and G‐4 were evaluated in the cisplatin‐sensitive ovarian cell line CH1/PA1 as well as in rather cisplatin‐insensitive colon (SW480) and lung (A549) carcinoma cells by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assays. Although the free platinum(IV) compound displayed a rather moderate activity, the drug–dendrimer complexes showed load‐ and size‐dependent behaviour with IC50 values down to the low‐nanomolar range. In the cisplatin‐insensitive cell lines, the benefit of this platinum load primarily consists of added cytostatic rather than cytocidal effects, on the basis of the results from annexin V/PI (PI = propidium iodide) assays for apoptosis/necrosis induction. Abstract : An unsymmetrically carboxylated platinum(IV) analogue of oxaliplatin is coupled to generation two (G‐2) and four (G‐4) polyamidoamine (PAMAM) dendrimers. The platinum–dendrimer complexes showed load‐ and size‐dependent potency with IC50 values down to the low‐nanomolar range, in contrast to the rather moderate activity of the free platinum(IV) compound.